DYNAMICS OF DEVELOPMENT OF BODY COGNITION THROUGH ARTISTICAL EXPRESSION OF BLIND AND LOW VISION CHILDREN - Lapeniene, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article actualizes the problem of overcoming learning difficulties in visually impaired conditions. Considering artistic activity as an integrative part of teaching – learning process, it seeks opportunities for the development of cognition of their body and active interaction with the environment. For the development of the cognitive activity of blind and low vision children by using the plastic expression is based on D. A. Kolb’s learning from the own experience model. For the research was conducted following steps: particular experience is acquired, this experience is cogitated and activated by verbal and kinaesthetic forms (it is described and expressed with the help of the move of the body), the experience is expressed with a new form: a clay work, the process of claying is reflected. The research was carried out in Educational centre for Partially Sighted Children. Respondents were six 7-11 years old born blind or low vision children the attention was concentrated not on the age but on the level of expression to which the work of the child was classed. Visually impaired children by versatile experience reflected on their own body cognition and these various experience process merged into one-unit kinaesthetic expression and reflection.